Better Nate than ever - Federle, Tim. (New York : Simon & Schuster Books for Young Readers, 2013)
An eighth-grader who dreams of performing in a Broadway musical concocts a plan to run away to New York and audition for the role of Elliot in the musical version of "E.T."
Sequel: Five, six, seven, Nate!
Ages 9-13.
English Language & Literature.
Keywords: Musicals -- Fiction; Theater -- Fiction; Auditions -- Fiction; Broadway (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction